2012
DOI: 10.1186/1758-5996-4-2
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic cerebral vascular response to sildenafil in diabetic patient

Abstract: BackgroundErectile dysfunction is a common problem in type 2 diabetic patients who are at higher risk of cerebrovascular events, and it's recorded with sildenafil, a drug which is primarily used for erectile dysfunction.ObjectivesWe tested the hypothesis whether or not sildenafil modulates cerebrovascular reactivity (CVR) in patients with type 2 diabetes mellitus.MethodsA total of 35 male participants were enrolled; eighteen with type 2 diabetes mellitus matched with seventeen normal individuals. Transcranial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 23 publications
5
18
0
Order By: Relevance
“…This concurs with Mandosi et al (16) who found out that sildenafil exerted a beneficial effect on glycometabolic control in type 2 diabetes by increasing insulin sensitivity (17). Moreover, the combination of sildenafil and insulin may offer an improved cerebrovascular response (18), due to its relaxation action on corpora cavernosa.…”
Section: Resultssupporting
confidence: 86%
“…This concurs with Mandosi et al (16) who found out that sildenafil exerted a beneficial effect on glycometabolic control in type 2 diabetes by increasing insulin sensitivity (17). Moreover, the combination of sildenafil and insulin may offer an improved cerebrovascular response (18), due to its relaxation action on corpora cavernosa.…”
Section: Resultssupporting
confidence: 86%
“…Of note, this study is an extension to our previous article published in this journal where modulatory effect of sildenafil on middle cerebral artery (MCA) was investigated in the same subjects. 17 …”
Section: Methodsmentioning
confidence: 99%
“…Pulsatility index and resistive index may reflect the compliance of the vessel and therefore, high PI and/or RI may indicate increase vascular resistance and increase in arterial stiffness [15,16]. Previous studies showed that diabetic patients have higher resistive index than normal population and this may increase micro-and macro-vascular complications [32].…”
Section: Discussionmentioning
confidence: 99%
“…To obtain MCA spectral wave form, probe is directed backward and slightly upward. The pulse wave Doppler sample volume was adjusted to maximum level in the device and the power 75 MW for identification and localization of middle cerebral artery spectral waveform [32,33]. To recognize the waveform of middle cerebral artery, the waves are above zero line in spectral wave display screen.…”
Section: Methodsmentioning
confidence: 99%